ADOPSI KECERDASAN BUATAN DALAM RUANG REDAKSI TVRI JAWA TENGAH DAN TVKU SEMARANG - Roesdita Surya Pramei; Lintang Ratri Rahmiaji (Interaksi Online, 2026)
The development of artificial intelligence (AI) technology has driven transformation in the media industry, including in television news production. This study aims to analyze the adoption of AI in the newsrooms of TVRI Central Java and TVKU Semarang and to understand how this technology is used in news production and the implementation of journalistic ethics policies. This study used a descriptive qualitative approach with a constructivist paradigm. Data were obtained through in-depth interviews with six informants, including editors-in-chief, editors, and reporters from TVRI Central Java and TVKU Semarang. The analysis was conducted using the Hierarchy of Influences theory by Pamela J. Shoemaker and Stephen D. Reese. The results show that AI adoption at both stations is selective and asymmetrical. AI is utilized at the gathering stage for initial research, at the scriptwriting stage as a transcription aid, and at the visualization stage in the form of animated graphics and visual presenters. Significant differences exist in ethics policies: TVRI Central Java has a more formal governance system with mandatory AI content labeling through the Director's Regulation (Perdiri), while TVKU relies on individual initiative without a specific written policy. Overall, AI functions as augmentation that strengthens journalists' capacities, not as a replacement for humans in the news production process.